스마트폰 기반의 지능형 태양광 전력적산 모니터링 시스템에 관한 연구 - 김관형(Gwan-Hyung Kim) (한국정보통신학회논문지, 2016)
Smart grid technology can be called grid techniques to improve the efficiency of the electric power by exchanging bidirectional information of electric power with real-time between electric power suppliers and consumers. Recently, the solar power generation system is being applied actively. However the solar power system has several problems leading to reduce overall electricity generation, because the difficult of the diagnosis and the solar power system failure such as PV(PhotoVoltaics) and inverter. In order to build an efficient smart grid, a stable electric power energy requirements capture and management and early fault detection is essentially required in solar power generation system. In this paper, it is designed to monitor the operating status of the solar power monitoring system from a remote location through a RS-485 or TCP/IP communication module to monitoring the output of solar power energy and abnormal phenomenon, to developing the measurement module and to transfer measured data. 스마트 그리드(smart grid) 기술은 전력 공급자와 소비자 사이를 실시간으로 전력정보를 교환함으로써 전력의 효율성을 높이는 전력망 관리 기술이다. 최근에는 유지보수 및 설치가 용이한 태양광 발전시스템에 대한 적용이 늘고 있다. 그러나 태양광 발전 시스템은 고장진단이 어려우며, PV(PhotoVoltaics) 어레이 및 인버터(inverter) 등의 결함과 기타 잠재적인 출력저하 요소로 인하여 발전량이 감소하기도 한다. 이처럼 태양광 발전 시스템을 통하여 안정적인 에너지 포집과 관리 및 조속한 고장 검출이 필수 요구사항이라 할 수 있다. 본 논문에서는 태양광 발전 시스템을 대상으로 전력 생산량 및 이상 동작 현상을 모니터링하고 외부 환경을 계측하는 계측모듈을 개발하고, 계측된 정보 데이터를 전송할 수 있는 통신모듈을 통하여 원격지에서 태양광 발전 시스템의 동작 상태를 모니터링 하도록 설계하였다. 또한 스마트폰을 기반으로 구축된 태양광 발전 시스템을 실시간으로 관리하고 모니터링 할 수 있는 모바일 관리 시스템을 제시하고자 한다.